The Use of Animated Videos In Teaching Vocabulary For Young Learners - Dewi Fortuna Setiawati; Ayu Rizki Septiana (Wanastra: Jurnal Bahasa dan Sastra, 2022)
Abstract  - English has an important role in correspondence around the world so that it becomes a global language that is understood by all nations in the world. Therefore, it is important to teach English from an early age. One of the things that teachers need to pay attention to in teaching early childhood is learning media. Animated video itself is one of the learning media that can be applied as a learning medium for young learners. In this study, the researcher wanted to analyze the effect of learning media using animated videos in teaching English to young students, especially vocabulary mastery. From the calculation using SPSS 16.0, data were obtained based on descriptive statistics, namely, the average pretest was 53.750 and the posttest average was 73.375. This indicates an increase in the average value from pretest to posttest. In addition, the pretest score shows a minimum score of 45 students and a maximum score of 72.5 students. and experienced an increase in the posttest score, namely the student's minimum score of 65.0 and the maximum student's score of 87.5. The hypothesis testing using paired sample test showed that the significance value is lower than the level of significance (0.000 < 0.05). Thus, it can be concluded that there is a significant difference in students' vocabulary mastery before and after being taught using animated videos